Extraction of Boron with Diols in Petroleum Benzine andfat n-Amyl Alcohol - Ozay, Pelin; Yurdakoc, Muruvvet; Karakaplan , Mehmet; HOSGOREN, HALIL (Asian Journal of Chemistry, 2012)
In the present work, the solvent extraction of boron with 2-ethyl-1,3-hexanediol (EHD), 1,2-dihydroxy-4-oxadodecane (DHD) and 3-(4-tert-butylphenoxy)-1,2-propanediol (BFPD) in petroleum benzine and n-amyl alcohol was thoroughly studied as a function of equilibrium pH. The pH 0.5 values for EHD, DHD and BFPD were determined from R %-pH graphs as 8.3, 2.7 and 2.3 in n-amyl alcohol, respectively. The extraction efficiencies of these diols were also comparatively investigated. The extraction efficiency in both solvents for each extractant was ranged from 78 to 98%. Stripping of boron was achieved as 96% for EHD with NaOH and 81% for BFPD with H2SO4.